2017
DOI: 10.1111/jpi.12427
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of high glucose‐induced PINK1 expression by melatonin stimulates neuronal cell survival: Involvement of MT2/Akt/NF‐κB pathway

Abstract: Hyperglycemia is a representative hallmark and risk factor for diabetes mellitus (DM) and is closely linked to DM-associated neuronal cell death. Previous investigators reported on a genome-wide association study and showed relationships between DM and melatonin receptor (MT), highlighting the role of MT signaling by assessing melatonin in DM. However, the role of MT signaling in DM pathogenesis is unclear. Therefore, we investigated the role of mitophagy regulators in high glucose-induced neuronal cell death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 71 publications
0
41
0
Order By: Relevance
“…Intracoronary melatonin boosts coronary blood flow and cardiac function in anesthetized pigs, and this effect could be abolished by an MT2 receptor‐specific inhibitor 4‐P‐PDOT . In another report, melatonin improved neuronal cell survival in response to high‐glucose insult through PINK1 activation and resultant preservation of mitochondrial function, the effect of which could be abolished by MT2 receptor‐specific inhibitor 4‐P‐PDOT . Such data comprising tissue‐ and isoform‐specific effects of melatonin receptors are constructive in the development of the tissue‐ or isoform‐specific MT2 pharmacological activators for treating diverse pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Intracoronary melatonin boosts coronary blood flow and cardiac function in anesthetized pigs, and this effect could be abolished by an MT2 receptor‐specific inhibitor 4‐P‐PDOT . In another report, melatonin improved neuronal cell survival in response to high‐glucose insult through PINK1 activation and resultant preservation of mitochondrial function, the effect of which could be abolished by MT2 receptor‐specific inhibitor 4‐P‐PDOT . Such data comprising tissue‐ and isoform‐specific effects of melatonin receptors are constructive in the development of the tissue‐ or isoform‐specific MT2 pharmacological activators for treating diverse pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Onphachanh and colleagues demonstrated that melatonin stimulates PINK1 expression via the MT2/Akt/NF-κB pathway, which is important for the prevention of neuronal cell injury under high glucose conditions. 37 Our previous study also demonstrated that melatonin alleviates cardiac remodelling and dysfunction in DCM. 38…”
Section: Introductionmentioning
confidence: 88%
“…Melatonin elevates the expression of nuclear factor erythroid 2related factor 2 (Nrf2) resulting in the up-regulation of the expression of phase II antioxidant/detoxifying enzymes such as heme oxygenase-1 (HO-1) decreasing oxidative stress and activation of nuclear factor-κB (NF-κB) cascade [158].The expression of PINK1 and microtubule-associated proteins 1A/1B light chain 3 B (LC-3 B), mitophagy markers, increased in neuronal cells following treatment with melatonin. Since silencing of PINK1 expression impairs melatonin-mediated reduction of mitochondrial ROS production and apoptotic marker activation, it is suggested that melatonin prevents neuronal cell apoptosis under high glucose conditions through stimulating PINK1 expression; this effect of melatonin has been demonstrated to be MT2 receptor dependent [159].…”
Section: Therapeutic Potentials Of Melatonin For Diabetic Neuropathymentioning
confidence: 99%
“…In hyperglycemia state, the persistent oxidative stress contributes to damage to the nuclear DNA and the mitochondrial genetic material [168]. Anti-apoptotic effects Antioxidant effects [159] Page 12 of 20 Pourhanifeh et al Diabetol Metab Syndr (2020) 12:30 Hyperglycemia leads to apoptosis in different types of cells in diabetic nephropathy, such as the proximal tubule epithelial cells [169]. It has been previously explained that the apoptosis occurs through activating numerous intracellular signaling pathway [170].…”
Section: Melatonin Is An Appropriate Agent For the Treatment Of Diabementioning
confidence: 99%